Face injury by elastomer ammunition with important sequel: case report and brief literature review (Research, Society and Development, 2020)
Gunshot wounds are situations that require unique care in their treatment. Currently, the number of accidents resulting from the use of firearms is increasing and this reflects a need for a safe and efficient approach to these cases. Thus, the maxillofacial surgeon should evaluate the patient as soon as possible and plan the treatment effectively, avoiding undesirable consequences such as infections and impairment of primary functions such as vision. This work aims to report a case in a qualitative and descriptive manner, in which the individual attended the service presenting a firearm injury with elastomer ammunition, thus addressing and discussing the singularities, complications, and forms of treatment for such types of injuries, in order to consolidate and suggest a possible consensus on the subject.